Dampak Pengeluaran Pemerintah terhadap Pertumbuhan Ekonomi di Kota Solok - Luba, Annisa Tiara; Lestari, Lika; Rasmi, Rasmi (Lembaga Yasin AlSys, 2023)
Economic growth is an indicator of the success of economic development. To trigger economic growth, the state has a very significant contribution in controlling the economy, one of which directly affects the economic growth of Solok City through state spending. The effect of state spending on economic growth in the city of Solok. The purpose of this study is to analyze the impact of public spending on economic growth in Solok City, using secondary data from the Central Statistics Agency (BPS) for 2020-2022. The result of this study is a positive report on public spending by the Central Bureau of Statistics (BPS) for the City of Solok in 2020-2022 which shows that the city's public spending has increased every year for two years. up to one year in a year in Until 2020 government spending in Solok City was 18.23 percent, in 2021 government spending grew by 7.21 percent, and in 2022 government spending also grew by 8.15 percent. The increase in spending in the Solok city government sector is due to growth from year to year, and the government also requires larger funds or budgets for the economic growth of the city of Solok.